Issues of Marketing Development in the Market of Personal Services - Musayeva Shoira Azimovna (Antis Publisher, 2024)
This article examines the market of household services, reproduction, a complex and self-regulating socio-economic system, the constant influence of all its links on supply and demand of the population, as well as its center, that is, the interests of the service consumer, the task of a target indicator for all service enterprises.